Повзучість трійникового з'єднання трубопроводу при спільній дії температурно-силових та радіаційних полів - Бреславський, Дмитро Васильович; Пащенко, Сергій Олександрович (НТУ "ХПІ", 2018)
У статті надано математичну постановку трьохвимірної задачі повзучості, що відбувається при дії температурно-силових та радіаційних полів. Для розв'язання задачі прийнято метод скінченних елементів, що використовується спільно з різницевим методом інтегрування за часом. Для чисельного аналізу застосовано розроблений програмний комплекс, що використовує восьмивузловий об’ємний скінченний елемент. Досліджено вплив повзучості та радіаційного розпухання на напружено-деформований стан фрагменту системи охолодження ядерного реактору. Встановлено, що отримані розв'язки для задач температурно-силової повзучості та радіаційного розпухання у районі стику труб є принципово відмінними від результатів комплексного розв'язку. Розрахунками виявлено, що вплив радіаційного розпухання істотно уповільнює релаксацію напружень при повзучості та підвищує їхній рівень у місці стику труб.

The mathematical statement of three-dimensional problem of creep, which is running under the action of temperature, force and radiation fields, is presented in a paper. The total strain is considered as a sum of elastic, temperature, creep and swelling parts. The nonhomogeneous temperature fields are considered for determining the strain distribution as well as for obtaining the value of the neutron fluence function. The case of long term deformation under the creep with isotropic properties was analyzed by use of Norton law. The Finite Element Method, which is used jointly with finite differences method for time integration, was accepted for the problem’s solution. The volume finite element with eight nodes is used in numerical analysis. The approach uses the algorithm of parallel computing for the system of linear algebraic equations, which is solved by Choletski method. The program complex in C++ programing language was developed in order to realize the method and algorithms. It has been applied for numerical analysis. The influence of creep and radiation swelling on the stress-strain state of the cooling system fragment from nuclear reactor was investigated. The von Mises stress distributions are presented for different cases of nonlinearities both for tube’s volume and for the place of stress concentration. It was established that obtained solutions for the separate problems of creep under irregular temperature field and inner pressure as well as for problem of radiation swelling significantly differ from the solution of complex problem with consideration of both effects. It was found by numerical simulation that influence of radiation swelling significantly decreases the stress relaxation in creep conditions and increases the stress level in the place of tubes joint.
Creep of t-joint of pipeline under joint action of temperature-force and radiation fields
Keywords: повзучість; радіаційне розпухання; рівняння стану; ядерний реактор; трійникове з'єднання трубопроводу; метод скінченних елементів; temperature; radiation swelling; constitutive equations; nuclear reactor; t-joint of pipeline; finite element method; creep